A REFLECTION ON QUEERCRIP CHILD AND YOUTH CARE PRACTICE: DREAMS OF CARE AND FUTURITY - Gemar, Casper (International Journal of Child, Youth and Family Studies)

(untitled) (University of Victoria, 2021)
This paper engages with a reflection on the author’s embodied queercrip youth care praxis. The author uses queercrip theory to examine child and youth care practices and the relationships they hold to structures of power and domination. In so doing, he uses the terms eliminatory logics, survival dreaming, and crip constellations to understand the dynamics that undergird care and liberatory futures. Exploration of the (re)emerging queercrip paradigms that are the foundation of this work finds that these practices of care require moving beyond current imaginaries in youth care spaces. The paper concludes with recommendations for practice.